On the Implementation of Transfers to Subnational Governments - Searle, Bob (IMF Working Papers; Working Paper, 2005)
This paper examines a typology of grants that are used across the world, and places these in the context of the overall constitutional and legal framework for a country. It looks at the options for grants, given the need to maintain overall macroeconomic stability, efficiency in the use of scarce resources as well as reduced horizontal disparities. The role of central objectives in a decentralized framework is also assessed. The paper argues for a comprehensive framework for grants, as well as a proper institutional framework to manage grants systems.